1998
DOI: 10.1021/jp9806260
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Solvation Effects on the Structures and Properties of Adenine−Uracil Complexes:  A Theoretical ab Initio Study

Abstract: Ab initio quantum chemical studies at the HF level with the 6-31G* basis set were performed for three different Watson−Crick hydrogen bonded adenine−uracil complexes in the gas phase and in a water solution approximated by the first solvation shell. Full geometry optimizations without any constraints on the planarity of these complexes were carried out. The solvent effect was modeled by explicit inclusion of seven water molecules which creates the first coordination sphere around the adenine-uracil base pair. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 38 publications
8
71
0
1
Order By: Relevance
“…This structure is 7.5 kcal/ mol less stable than the canonic AT pair. These predictions are in complete correspondence with the results published in ref 37 and those obtained in the current investigation. Similar results have been obtained for the hydration of the GC base pair.…”
Section: Stabilizing and Destabilizing Factors For The Doubleproton Tsupporting
confidence: 93%
See 1 more Smart Citation
“…This structure is 7.5 kcal/ mol less stable than the canonic AT pair. These predictions are in complete correspondence with the results published in ref 37 and those obtained in the current investigation. Similar results have been obtained for the hydration of the GC base pair.…”
Section: Stabilizing and Destabilizing Factors For The Doubleproton Tsupporting
confidence: 93%
“…A similar investigation has been performed in our previous study at the MP2/6-31G(d)//HF/6-31G(d) level for the hydration of the AU, A*U*, CiC, and C*iC* base pairs (iC denotes isocytosine, which has the same structural pattern as the sixmembered heterocyclic part of guanine). 37 The results of the relative energies obtained previously 35 can be very easily explained using the maps presented in Figures 5 and 6 and, therefore, applied directly to the currently studied base pairs. However, to clarify the discussion, it should be mentioned that only the data concerning the positions of water molecules obtained previously have been used to construct the initial aqueous hydration shells surrounding the AT, A*T*, GC, and G*C* DNA base pairs.…”
Section: Stabilizing and Destabilizing Factors For The Doubleproton Tmentioning
confidence: 76%
“…It was found that the elongation of the C=O bonds could reach up to 0.02 Å , and changes in the geometry of the amino group due to the formation of the hydrogen bonds is notable. The same results have been obtained for adenine-uracil, isocytosine-cytosine, and guanine-cytosine base pairs interacting with several water molecules [20,21].…”
Section: Introductionsupporting
confidence: 81%
“…Therefore the result supports C 3 H 4 N 2 O + production from multi-photon ionized uracil-adenine complexes. Zhanpeisov and Leszczynski [42] and…”
Section: Fig 5 Compares Mpi and Eii Measurements Carried Out On Uracmentioning
confidence: 99%